Los programas de derecho internacional público : su evolución en la Facultad de Derecho de la Universidad de Buenos Aires desde 1955 - Godio, Leopoldo M. A. (2015)
The present report examines the main challenges facing higher education of Public International Law. For this purpose, an evaluation of those, including the evolution of the main strategic programmes, since 1955, and offering some suggestions for their improvement at Buenos Aires University Law School.